2000
DOI: 10.1002/1522-2675(20000906)83:9<2464::aid-hlca2464>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Fluorescence Properties of Novel Transmembrane Probes and Determination of Their Orientation within Vesicles

Abstract: Ein kontinuierlicher Wechsel zwischen magnetischen High‐Spin‐ und Low‐Spin‐Zuständen wird durch Einstrahlen von rotem bzw. grünem Laserlicht erreicht. In der Zuschrift auf berichten S. R. Batten et al. über ein Metallosupramolekül, bei dem durch Temperaturwechsel oder durch Einstrahlen von Licht ein Spin‐Crossover(SCO)‐Schalten möglich ist. Das SCO‐Verhalten hängt zudem von der Gegenwart und der Art eingeschlossener Lösungsmittelmoleküle in der porösen Kristallstruktur ab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…These absorption spectral features are similar to those of a 2,6-diethynylanthracene derivative reported in a previous study. [49] The existence of the monomeric state for 1 in chloroform (10 À3 M) is supported by the results of infrared measurements (see Supporting Information). The emission spectrum of 1 in chloroform (10 À3 M) (Fig.…”
Section: Absorption and Luminescent Properties In Solutionmentioning
confidence: 63%
“…These absorption spectral features are similar to those of a 2,6-diethynylanthracene derivative reported in a previous study. [49] The existence of the monomeric state for 1 in chloroform (10 À3 M) is supported by the results of infrared measurements (see Supporting Information). The emission spectrum of 1 in chloroform (10 À3 M) (Fig.…”
Section: Absorption and Luminescent Properties In Solutionmentioning
confidence: 63%
“… a λ, ε, and τ are given in nm, 10 3 M −1 cm −1 , and ns respectively b Only ε values for the most intense peak are given. c Data extracted from graphs 197 d

Only a spectroscopic study in dimyristoylphosphatidylcholine (DMPC) vesicles is reported, λ abs and λ em are extracted from graphs, and only the most contributing τ is given.

…”
Section: Figuresmentioning
confidence: 99%
“…[5] Some transmembrane bolaamphiphiles have been produced previously for altering specific membrane properties: for example, compounds with p-benzoquinone or anthraquinone groups to change the redox behavior, [6] or conjugated polyenes derived from the natural product bixine to modify the charge-transfer rate across the bilayer. [7] Furthermore, bolaamphiphiles that contain photochemically reactive benzophenone [8] or diazirine [9] groups, or emitting fluorene [10] or anthracene groups, [11] have been also synthesized. A different but interesting fluorescent bolaform structure was also produced by linking two rhodamine 101 dye molecules with a C 32 linear chain.…”
mentioning
confidence: 99%